NUTRITIVE VALUE OF BARLEY SILAGE (Hordeum vulgare L.) WITH DIFFERENT LEVELS OF SACCHAROMYCES CEREVISIAE AT DIFFERENT ENSILING LENGTHS - & et al., Contreras (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The objective of this study was to evaluate the effects of yeast (Saccharomyces cereviceae) as additive for barley silage preparation at different ensiling times. Small scale silages were prepared from barley forage and four yeast levels were evaluated (0 (control), 5, 10 and 15 g/kg FM). Silos were opened at 6, 12 and 24 days. Three silage-replicates were prepared for each yeast level × ensiling time combination. Silage quality in terms of CP and NDF and ADF concentration appeared to improve when yeast was added at 5 and 10 g/kg, compared with the control, but the quality decreased again when 15 g yeast/kg FM were aded to the silage. However, gas production, metabolisable energy and organic matter digestibility linearly decreased by yeast addition. This indicates a likely negative effect of yeast over the fermentation process during fermentation of barley silage. No time effects were observed for most of the parameters with the exception of ether extract concentration. Based on the results of this study, yeast addition is detrimental to the nutritional quality of barley silage. Mechanisms for this still remain unknown, but an undesirable fermentation provoked by yeast addition might be an explanation for our findings.